Distributing legitimacy: the politics of milk in post-World War II Venezuela. Issue 1 (2nd January 2019) - Hamilton, Shane
ABSTRACT: Questions of how best to feed the urban masses in an economy largely dependent on petroleum have permeated Venezuela's domestic and international political spheres since World War II. A state-initiated project, run by American capitalists under the direction of Nelson Rockefeller, developed Venezuela's milk distribution system into one of the country's most important agrifood industries by the late 1960s. The ways in which the firm navigated complicated questions of legitimacy and trust in public and private organizations provide an illustrative example of the inherently complicated relationship between state and business in the political economy of food distribution.